Root cell growth and division in soybean in the presence of base trichoderma and "Bradyrhizobium japonicum" bioproducts - Cadore, Luana da Silva; Trapp, Kássia Cauana; Vey, Rosana Taschetto; Dotto, Lucas; Tedesco, Solange Bosio; Silva, Antonio Carlos Ferreira da (Ciência e Natura, 2020)
The objective of this work was to evaluate the effect of commercial formulations of biological products on mitotic index and root growth, as well as on the initial development of soybean crop. A soybean cultivar Nidera 5909 was used, composed of four commercial bioformulates that had in its composition Trichoderma harzianum, Trichoderma sp. Bradyrhizobium japonicum. The products used were tested in combination or isolated for soybean seed inoculation in a randomized experimental design. In the variable length of shoot using Trichoderma sp., B. japonicum peat and Trichoderma sp. associated with B. japonicum peat did not differ from the control treatment but differed from the others. There was an increase in root length of soybean seedlings for the treatments T. harzianum + B. japonicum liquid and T. harzianum + B. japonicum peat compared to the control, as well as an increase in the mitotic index for the same treatments. The treatments T. harzianum + B. japonicum liquid and T. harzianum + B. japonicum provided higher root growth of soybean seedlings and higher initial plant growth.